A practical guide for the computation of domain-level estimates with the Socio-Economic Panel (and other household surveys) - Natascha Hainbach; Christoph Halbmeier; Timo Schmid; Carsten Schröder (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
There is a huge interest in deriving and comparing socio-economic indicators across societal groups and domains. The indicators are usually derived from population surveys like the German Socio-Economic Panel (SOEP) by direct estimation. Small sample sizes in the domains can limit the precision of these estimates. For example, while SOEP may be a suitable database for determining mean income in Germany, it is unclear whether this also applies to smaller domains (for example, women in Berlin). Here we show SOEP-based applications of Stata's fayherriot package (Halbmeier et al., 2019). This package implements the Fay-Herriot model (Fay and Herriot, 1979), a small-area estimation technique designed to improve the precision of domain-level direct estimates using domain-level covariates from auxiliary datasets.
Keywords: C13; C31; C51; C87; 330; Disaggregated indicators; Small area estimation; Fay-Herriot model; Socio-Economic Panel